2007
DOI: 10.1037/1528-3542.7.4.882
|View full text |Cite
|
Sign up to set email alerts
|

Fearful expressions gain preferential access to awareness during continuous flash suppression.

Abstract: Rapid evaluation of ecologically relevant stimuli may lead to their preferential access to awareness. Continuous flash suppression allows assessment of affective processing under conditions in which stimuli have been rendered invisible due to the strongly suppressive nature of dynamic noise relative to static images. We investigated whether fearful expressions emerge from suppression into awareness more quickly than images of neutral or happy expressions. Fearful faces were consistently detected faster than ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
431
8
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(477 citation statements)
references
References 32 publications
37
431
8
1
Order By: Relevance
“…After all, in other circumstances suppression durations of a visual stimulus are impacted by the properties of that stimulus, including its physical characteristics (9), its configural properties (30,66), its affective connotation (67,68), its lexical familiarity (32), and its social connotation (69). However, in all these instances the features defining the suppressed stimulus are plausibly being registered and remain available for analysis (70), albeit with reduced fidelity or signal strength (34).…”
Section: Discussionmentioning
confidence: 99%
“…After all, in other circumstances suppression durations of a visual stimulus are impacted by the properties of that stimulus, including its physical characteristics (9), its configural properties (30,66), its affective connotation (67,68), its lexical familiarity (32), and its social connotation (69). However, in all these instances the features defining the suppressed stimulus are plausibly being registered and remain available for analysis (70), albeit with reduced fidelity or signal strength (34).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that object information is processed without awareness during interocular suppression (Jiang et al, 2007;Yang et al, 2007;Zhou et al, 2010;Mudrik et al, 2011;Stein et al, 2011aStein et al, ,b, 2012Stewart et al, 2012). For instance, upright faces (Jiang et al, 2007;Zhou et al, 2010;Stein et al, 2011aStein et al, , 2012, faces with direct gaze (Stein et al, 2011b;Yokoyama et al, 2013), or fearful faces (Yang et al, 2007;Stein et al, 2014) break suppression faster than inverted faces, faces with averted gaze, or neutral faces, respectively. In addition, incongruent scenes (e.g., soccer players dribbling a watermelon instead of a soccer ball) are detected faster than congruent scenes (Mudrik et al, 2011).…”
Section: Location Uncertainty Can Facilitate Unconscious Processing Imentioning
confidence: 99%
“…Natural images are reported to be dominant over unnatural images in binocular rivalry [84], as are images of emotional over (more) neutral faces or scenes [85][86][87] and upright faces over inverted ones [88]. The personal preferences or mental condition of the observer [89 -91], as well as their cultural background or religion can also influence particular forms of rivalry [92].…”
Section: Context Of Internal Statementioning
confidence: 99%